Stability and change of verbal ability from adolescence to early adulthood: The longitudinal twin study - Bratko, Denis (Array, 2003)
The aim of the study was to explore the stability and change in verbal ability from adolescence to early adulthood. The sample consisted of 125 same-sex twin pairs (55 identical and 70 fraternal twin pairs ; 71 male and 54 female pairs). The sample was recruited through the population registry, and it was representative for the city of Zagreb, Croatia. The age of twins at the first measurement point varied from 15 to 19 years (M=17.25 ; SD=1.327). The test-retest interval was exactly 4 years. The two factors of verbal abilities were measured: word fluency and vocabulary. The results indicate substantial four-year stability of individual differences. Phenotypic test-retest correlations were .71 and .74 for word fluency and vocabulary, respectively. As expected, mean scores in the second measurement point increased. Heritabilities of the measures were substantional, both for the first and the second measurement points. Longitudinal analysis indicates that phenotypic stability of individual differences from adolescence to early adulthood is genetically mediated.